The Influence of Problem-Based Learning on Students’ Mastery of The Simple Past Tense: A Study of Second-Semester English Education Students at San Pedro University: Penelitian - Denitriana Ut; Miss Rozita Yusniaty Lodo; Mansuetus Mola (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research investigates the effects of implementing Problem-Based Learning (PBL) on the grammatical competence of second-semester students majoring in English Education at San Pedro University. Employing a quasi-experimental design, the study involved dividing participants into experimental and control groups, with the former receiving instruction through PBL while the latter utilized conventional methods. Assessments included pre-tests and post-tests to gauge proficiency in the simple past tense, alongside qualitative measures like classroom observations and student reflections. Findings from quantitative analysis indicated marked enhancements in the experimental group's performance, evidenced by elevated mean scores and reduced variability, suggesting PBL's efficacy in fostering deeper understanding and application of grammatical rules. Qualitative insights further revealed heightened engagement and motivation among learners. Overall, the results underscore PBL's potential as a transformative approach in language pedagogy, recommending its adoption for grammar instruction to cultivate not only accuracy but also communicative skills and learner independence.